Geotechnical evaluations of Haliç's sedimentary layers - Köseler, Mahir. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1984., 1984)
The presence of soft layers in Haliç create a great deal of geotechnical problems during the dredging of Haliç. It is necessary to make geotechnical evaluations to prevent critical situations during dredging. The general geology and soil conditions in the area are studiedo Geological formation along Haliç is given by geological cross-sections. Geotechnical properties of these layers are documented. The environmental problems in the vicinity of Haliç and dredging of Haliç are investigated. Since the layers(bottom sludge and underlying clay formation) are very soft and weak, stability of the shores should be considered before dredging. So stability of slopes is studied and the computer program for slope stability (KOSELER-I) are given. Some geological and geotechnical conclusions and recom- mendations such as what can we do to prevent critical situations that may arise before dredging and during dredging are given.
Keywords: Water -- Pollution -- Turkey -- Haliç.; Soil mechanics -- Turkey -- Haliç.; Slopes (Soil mechanics) -- Computer programs.